Culturing Bacteria From Fermentation Pit Muds of Baijiu With Culturomics and Amplicon-Based Metagenomic Approaches - Xu, Jialiang; Sun, Leping; Xing, Xuan; Sun, Zhanbin; Gu, Haoyue; Lu, Xin; Li, Zhenpeng; Ren, Qing (Frontiers in Microbiology, 2020)
The Baijiu-making microbiota has an important role in the alcohol production, flavor and character of Baijiu. 16S rRNA gene sequencing revolutionized the understanding of Baijiu-making microbiota. In this study, 9 phyla, 23 classes, 49 orders, 99 families and 201 genera were detected in pit muds by 16S rRNA gene sequencing. Firmicutes and Bacteroidetes predominated (>99%). At the order level, Clostridiales, Bacteroidales, and Bacillales predominated (>92%). At the genus level, Hydrogenispora, Petrimonas, Proteiniphilum and Sedimentibacter predominated. The pure culture of Baijiu-making prokaryotes was essential to elucidating the role of these microbes in the fermentation of Baijiu. According to the theory of microbial culturomics, a culturing approach with multiple culture conditions was adopted, combining 16S rRNA gene sequencing. We identified 215 prokaryotic strains, which were assigned to 66 species, 41 genera, 4 phyla and 19 potential new species. Gas conditions were key factors in culturomics. In addition, culturomics significantly increased the number of species isolated from the fermentation pit mud (PM) compared with previous reports. With culturomics, the diversity spectrum of culturable bacteria in the PM was increased 273.33% at the genus level. This study confirms the complementary role of culturomics in the exploration of complex microbiota.